2008
DOI: 10.1253/circj.cj-08-0308
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Arch Calcification and Arterial Stiffness are Independent Factors for Diastolic Left Ventricular Dysfunction in Chronic Hemodialysis Patients

Abstract: Background Because cardiovascular disease is the major cause of death in dialysis patients, the correlation between diastolic left ventricular (LV) dysfunction and arterial sclerosis, including thoracic aortic calcification, was studied in chronic hemodialysis (HD) patients. Methods and ResultsThe enrolled study subjects were 142 (73 men, 69 women) maintenance HD patients. Aortic arch calcification volume (AoACV) was measured by MDCT scan, arterial stiffness was estimated by brachial -ankle pulse wave velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 36 publications
(36 reference statements)
5
51
0
1
Order By: Relevance
“…Vascular calcifications were observed in 55.7% of patients and related to left ventricular hypertrophy, diastolic dysfunction, cardiac valve calcification, ischemic heart disease and cardiac failure episodes. We also reported that the extent of AoAC and arterial stiffness were independent determinants of left ventricular diastolic function in chronic HD patients 26) . In the present study, the serum FGF-23 level was shown to be a significant predictor of Ca and P metabolism in chronic HD patients without diabetes.…”
Section: Aoacs (%)mentioning
confidence: 87%
“…Vascular calcifications were observed in 55.7% of patients and related to left ventricular hypertrophy, diastolic dysfunction, cardiac valve calcification, ischemic heart disease and cardiac failure episodes. We also reported that the extent of AoAC and arterial stiffness were independent determinants of left ventricular diastolic function in chronic HD patients 26) . In the present study, the serum FGF-23 level was shown to be a significant predictor of Ca and P metabolism in chronic HD patients without diabetes.…”
Section: Aoacs (%)mentioning
confidence: 87%
“…4 Previous reports have demonstrated that marked vascular calcification and stiffness predisposed hemodialysis patients to LVH and cardiac diastolic dysfunction. 21 We investigated the impact of fetuin-A and OPG serum levels, which are representative of potent vascular calcification regulators, on vascular stiffness and ventricular function. In hemodialysis patients, the levels of serum fetuin-A have been shown to be consistently low, probably due to its enhanced consumption 7 caused by the calcium phosphate load in addition to a chronic microinflammatory status.…”
Section: Discussionmentioning
confidence: 99%
“…6,28 Thus, we assume that FGF-23 is likely to correlate with LVH that is induced directly by hyperphosphatemia or indirectly via hyperphosphatemia-induced vascular calcification, which induces diastolic dysfunction in patients with chronic HD. 29 Further study is necessary to test these possibilities. In addition, a study to investigate whether the combination of the FGF-23 and BNP improves the prediction of mortality compared with FGF-23 alone is warranted.…”
Section: Fgf-23 As Novel Biomarker Of Cardiovascular Remodelingmentioning
confidence: 99%